Superfoods and their role in disease prevention - Szklarz , Magdalena; Bielak, Alicja; Gryta, Jakub; Radziejowska, Zuzanna; Iwan, Karolina; Kalicka, Maria; Kolasa, Agata; Janczewska, Martyna; Krysa, Tomasz; Ferschke, Anna (Quality in Sport, 2023)
Introduction and purpose Functional food also known by the term “superfoods” are rich in bioactive compounds with specific biological properties and due to that beneficial effects within the human body. Nowadays chronic degenerative diseases such as diabetes, cardiovascular disease, obesity and cancer are increasingly common in the population. Therefore the need to support treatment but also reduce the risk of these diseases in the first place increases as well. This is the reason for the great interest and growing trend in the consumption of superfoods, especially in Europe and the United States. The purpose of this article is to demonstrate the impact of selected superfoods on human health. State of knowledge Superfoods are considered nutrient-dense and rich in bioactive compounds that are beneficial for physical and mental health. Antioxidant activity is one of the most important properties for human health improvement. This activity is scavenging free radicals, thus preventing the development of various degenerative diseases. Today, more and more products are considered superfoods. Fruits, the examples of superfoods which will be discussed in this work, are well-available and require no heat treatment therefore incorporating them in one’s diet seems to be an easy way to improve health as a consequence. Summary The potential beneficial role of superfoods is considered in health promotion and even preventing the development of diseases. However, this can only be possible if superfoods are part of a balanced diet and healthy lifestyle. The following article is a review of current knowledge and data available in publications in Pubmed and Google Scholar databases related to correlation between selected superfoods consumption and disease prevention.